Combination drug delivery via multilamellar vesicles enables targeting of tumor cells and tumor vasculature. Issue 6 (6th March 2018) - Liu, Yarong; Kim, Yu J.; Siriwon, Natnaree; Rohrs, Jennifer A.; Yu, Zhiqiang; Wanga, Pin
Abstract: Blood vessel development is critical for the continued growth and progression of solid tumors and, therefore, makes an attractive target for improving cancer therapy. Indeed, vascular‐targeted therapies have been extensively explored but they have shown minimal efficacy as monotherapies. Combretastatin A4 (CA‐4) is a tubulin‐binding vascular disrupting agent that selectively targets the established tumor endothelium, causing rapid vascular beak down. Despite its potent anticancer potential, the drug has dose‐limiting side effects, particularly in the form of cardiovascular toxicity. Furthermore, its poor aqueous solubility and the resulting limited bioavailability hinder its antitumor activity in the clinic. To improve the therapeutic efficacy of CA‐4, we investigated its application as a combination therapy with doxorubicin (Dox) in a tumor vasculature targeted delivery vehicle: peptide‐modified cross‐linked multilamellar liposomal vesicles (cMLVs). In vitro cell culture studies showed that a tumor vasculature‐targeting peptide, RIF7, could facilitate higher cellular uptake of drug‐loaded cMLVs, and consequently enhance the antitumor efficacy in both drug resistant B16 mouse melanoma and human MDA‐MB‐231 breast cancer cells. In vivo, upon intravenous injection, targeted cMLVs could efficiently deliver both Dox and CA‐4 to significantly slow tumor growth through the specific interaction of the targeting peptide with its receptor on the surface of tumor vasculature. This study demonstrates the potential of our novel targeted combination therapy delivery vehicle to improve the outcome of cancer treatment. Abstract : In this study, cross‐linked multilamellar liposomal vesicles (cMLVs) were used to simultaneously deliver two drugs: one targeting the malformed tumor vasculature (CA‐4), and another targeting rapidly dividing tumor cells (Dox). The delivery of these drugs was enhanced by the conjugation of an Annexin A1 binding, D‐amino acid, reverse sequence peptide, RIF7, to the surface of the cMLVs. This peptide enabled targeted delivery of the cMLVs to the tumor vasculature, resulting in enhanced tumor regression in our mouse xenograft model.